Morphological variations in the anatomy of caecum and appendix - A cadaveric study - Arindom Banerjee; I Anil Kumar; Arunabha Tapadar; M Pranay (Wolters Kluwer Medknow Publications, 2012)
Background: Appendicitis is one of the most common clinical conditions that require emergency surgery. Variations in anatomical location of appendix can result in different clinical presentations. Anatomical and topographical variations of the caecum are also known to occur. Anatomical variations in caecum have been observed along with the appendix in this study. Aims: To study the variations in the size, shape, position and arterial supply of the caecum and appendix in individuals of different sex and age, a thorough knowledge of which will aid surgeons in performing various abdominal operations in adults and children. Material and methods: The study was carried out on 25 adult cadavers over a period of 3 years. The anatomy of caecum and appendix was studied in detail. Results: The normal position of caecum and appendix in adult cadavers was found to be in the right iliac fossa. In all specimens the shape of caecum was adult (ampullary) type and it was supplied normally in all cases from a branch of the superior mesenteric artery. The appendix was found in the retro-caecal position in majority of cases with a complete meso-appendix in four and an additional blood supply via the artery of Sesachalam was found in two cases. Conclusions: Vermiform appendix is characterized by variability of its location and morphology. The ultimate position of the appendix is influenced by the changes in position and shape which the caecum undergoes during development and growth. The present study observed the appendix and caecum to be found in their normal positions in majority of cases. The average length of caecum and appendix was found to be more in males as compared with females. Appendicitis is one of the most common diseases that need emergency surgery. Variations in anatomical position cause different clinical presentations. A thorough knowledge of normal anatomy and variations of the caecum and appendix is very important to the surgeon performing abdominal operations in adults, children and infants as it helps them to make optimal diagnosis of various pathological conditions related to these organs and treat accordingly.